Destination Attributes Affecting Negative Memory: Scale Development and Validation. (February 2022) - Kim, Jong-Hyeong
Previous researcher has discussed the significance of negative emotional experiences on consumer behavior. However, the extant memorable tourism experiences literature is preoccupied with discussing positive memorable experiences. To address this gap and to support destination managers, this study developed a scale that conceptualizes destination attributes associated with negatively memorable tourism experiences. Employing a multi-study method, this study identified a six-dimensional construct that influences negatively memorable tourism experiences. Multiple data supported the dimensional structure of this scale and confirmed its reliability, construct validity, discriminant, and predictive validity. Theoretical and managerial implications drawn from this study are discussed in detail.